Strategic Planning in Small Company - Pietras, Agnieszka; Szczepańczyk, Maciej (Lodz University of Technology Press, 2016)
In the current economic reality small companies must use the tools of strategic analysis in order to evaluate in a reliable way external and internal conditions which show their distinctive capabilities (assets) and the future chances and threats creating at the same time the conditions for building their competitive position. Therefore it can be stated that the future belongs to those companies which apply proper tools of strategic analysis and keep on improving them. This book presents a review of Polish and foreign literature taking into consideration the specificity of strategic management, strategic analysis, planning and a specificity of a small company. The published research results which refer to strategic management and strategic planning in small companies were used together with the material collected in own research conducted by means of surveys, free-form interview and a case study.
Redaktor Naukowy Wydziału Organizacji i Zarządzania: prof. dr hab. inż. Jerzy Lewandowski
Keywords: small companies; strategic analysis; strategic management; małe firmy; analiza strategiczna; zarządzanie strategiczne; planowanie strategiczne